2005
DOI: 10.1183/09031936.05.00127404
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent sarcoid granulomas in a transplanted lung derive from recipient immune cells: Fig. 1—

Abstract: From 1992From -2004, single lung transplantation has been performed in seven patients with end-stage pulmonary sarcoidosis at the Danish National Centre for Lung Transplantation. The objective was to assess whether recurrent sarcoid granulomas in the lung graft are derived from recipient or donor immune cells.Three patients had sarcoid recurrence in the lung graft, but none had clinically overt extrathoracic sarcoidosis. Graft sex-mismatch was present in one patient, a 52-yr-old female having a lung graft fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 14 publications
(13 reference statements)
0
14
0
Order By: Relevance
“…Epidemiologic data, including reports of case-clustering, increased susceptibility with certain occupations, and transmissibility via transplant, all support this theory (21,22). Infectious agents have long been suspected as possible causes of sarcoidosis, but early studies failed to yield convincing support for various organisms.…”
Section: Etiology and Pathogenesismentioning
confidence: 82%
“…Epidemiologic data, including reports of case-clustering, increased susceptibility with certain occupations, and transmissibility via transplant, all support this theory (21,22). Infectious agents have long been suspected as possible causes of sarcoidosis, but early studies failed to yield convincing support for various organisms.…”
Section: Etiology and Pathogenesismentioning
confidence: 82%
“…It is suggested that apoptosis (programmed cell death) may be associated with the course of granulomatous inflammation in pulmonary sarcoidosis (25). These processes depend on various, mostly unknown, genetic and environmental factors simultaneously (26,27). The influence of ethnic and genetic factors determines the heterogeneous clinical course of sarcoidosis (17).…”
Section: Discussionmentioning
confidence: 99%
“…Most commonly, sarcoidosis is discovered in donor solid organ allografts in recipients with a history of sarcoidosis [73][74][75][76][77][78][79][80], presumably inducing a granulomatous response by the recipient's immune system [81]. One report of sarcoidosis presenting following bone marrow transplantation suggests that this susceptibility may depend on donor MHC haplotypes [82].…”
Section: Models Of Sarcoidosis Pathobiologymentioning
confidence: 99%